P13 Silk Vista Baby Flow Diverter device (SVBFD) initial experience in a neuro-interventional Argentinean center. (29th August 2022) - Petra, F; Caballero, G; Graña, M; Fernandez, C; Horvath, F; Nazar, F; Alvarado, L; Genco, J; Parra, L; Galiana, G; Hungria, Santa Isabel de
Abstract : Background: FD stents had shown to be safe and effective in brain aneurysmatic pathology. New low-profile FD are allowing treatment of distal, small, parent-arteries aneurysms. Aim: To report our experience in the use of the SVBFD. Methods: Between August 2019 and April 2022, 39 patients were enrolled. Baseline clinical status, aneurysm/dissection morphology/morphometry, intra/post procedural technical details, modified Rankin Scale (mRS) at admission/discharge, Follow up MRI and angiographic results after treatment were collected (O Kelly Marotta Scale). Results: 39 patients (64, 10% female; 52.3yo mean-age; 28–75yo range) were enrolled and 45 aneurysms were treated, either alone or coil assisted. 29 patients (74.3%) were symptomatic while 10 (25, 6%) remained asymptomatic. Previous coiling was observed in 6 (13, 3%) cases, and concomitant coiling was performed in 8 (17, 7%) of the lesions treated. Adverse related events included side branch occlusion in 2, 2% (1/45) and in-stent thrombosis in 4, 44% (2/45). In 2, 2% of the cases (1/45), a 24 hours distal thromboembolic event was observed. At discharge, 84, 6% of the patients (33/39) showed a mRS of 0. Median Follow up of 22 months was achieved, by MRI/DSA in 100% of the patients. MRI Complete occlusion or small remnant was observed in 82% (37/45) and 4, 44% (2/45), respectively. DSA Complete occlusion OKM D was observed in 80% (36/45) or a small aneurysmal remnant, OKM C1-C3, in 6, 66% (3/45). Conclusion: The SVBFD is safe and effective, showing high occlusion rates and low complication adverse events, in the treatment of small/distal aneurysm. References: Bhogal P, Wong K, Uff C, Wadley J, Makalanda Hl. The Silk Vista Baby: Initial Experience and Report of Two Cases. Interv Neuroradiol 2019;25:530–8. 10.1177/15910199198391962. Martínez-Galdámez M, Biondi A, Kalousek V, et al . Periprocedural Safety and Technical Outcomes of the New Silk Vista Baby Flow Diverter for the Treatment of Intracranial Aneurysms: Results from a Multicenter Experience. J Neurointerv Surg 2019;11:723–7. 10.1136/Neurintsurg-2019-014770. Do you have any conflict of interest to declare? : No